PERBANDINGAN EFEKTIVITAS EKSTRAK Capsicum annuum L. (CABAI MERAH BESAR) SEBAGAI ANTIBAKTERI TERHADAP BAKTERI Staphylococcus aureus DAN Pseudomonas aeruginosa SECARA IN VITRO DENGAN METODE DIFUSI - Sundari Mahendrasari, (2014)
Indonesia as one of developing countries with infectious diseases as the leading cause of mortality and morbidity. Staphylococcus aureus and Pseudomonas aeruginosa are the most dangerous and also the most important bacteria among Staphylococcus and Pseudomonasgenus. Both of them are often resistant to many kind of drugs so that complicates selection of appropriate antimicrobial therapy. Capsicum annuum L. has antimicrobial effect and contain active chemical compound, such as alkaloid, saponin, flavonoid, triterfenoid, steroid, and glikosida. Capsaicin as the main compound of antibacterial. This kind of research is true experimental with a diffusion method, using Mueller Hinton Agar forS. aureus and P. aeruginosa. The result showed that the average of inhibition zone C. annuum L. extract for S. aureus growth at concentration 20%, 40%, 60%,80%, 100% are 0,81mm; 0,64 mm; 1,85 mm; 1,87 mm; and 3,31mm. Eventough,C. annuum L. extract againstP. aeruginosa growth at concentration 20 %,40%, 60%, 80% and 100% are 0,12 mm; 0,22 mm; 0,69 mm,1,1 mm, and 1,25mm. One Way Anova test (p < 0,05) showed that there was differences between each concentration for S. aureus and P. aeruginosa. Post Hoc test showed same effectiveness in some concentrations against S. aureus orP. aeruginosa. Independent t test showed (p>0,05) in conclusion, Capsicum annuum L. extract has same effectiveness for inhibition activity against S. aureus andP. aeruginosa.